A New Chaotic System with Stable Equilibrium: Entropy Analysis, Parameter Estimation, and Circuit Design - Kapitaniak, Tomasz; Mohammadi, S. Alireza; Mekhilef, Saad; Alsaadi, Fawaz; Hayat, Tasawar; Pham, Viet-Thanh (MDPI, 2018)
In this paper, we introduce a new, three-dimensional chaotic system with one stable equilibrium. This system is a multistable dynamic system in which the strange attractor is hidden. We investigate its dynamic properties through equilibrium analysis, a bifurcation diagram and Lyapunov exponents. Such multistable systems are important in engineering. We perform an entropy analysis, parameter estimation and circuit design using this new system to show its feasibility and ability to be used in engineering applications.